Urban-driven decrease in arthropod richness and diversity associated with group-specific changes in arthropod abundance - Chatelain, Marion; Rüdisser, Johannes; Traugott, Michael (Frontiers in Ecology and Evolution, 2023)
Habitat loss and fragmentation caused by land-use changes in urbanised landscapes are main drivers of biodiversity loss and changes in species assemblages. While the effects of urbanisation on arthropods has received increasing attention in the last decade, most of the studies were taxon-specific, limited in time and/or covering only part of the habitats along the rural-urban gradient. To comprehensively assess the effects of urbanisation on arthropod communities, here, we sampled arthropods at 180 sites within an urban mosaic in the city of Innsbruck (Austria) using a systematic grid. At each site, arthropods were collected in three micro-habitats: the canopy, the bush layer and tree bark. They were identified to the family, infra-order or order level, depending on the taxonomic group. Urbanisation level was estimated by five different proxies extracted from land use/land cover data (e.g. impervious surface cover), all of them calculated in a 100 m, 500 m and 1000 m radius around the sampling points, and three indexes based on distance to settlements. We tested for the effects of different levels of urbanisation on (i) overall arthropod abundance, richness and diversity, and (ii) community composition using redundancy analyses. In the canopy and the bush layer, arthropod richness and diversity decreased with increasing urbanisation level, suggesting that urbanisation acts as a filter on taxonomic groups. Our data on arthropod abundance further support this hypothesis and suggest that urbanisation disfavours wingless groups, particularly so on trees. Indeed, urbanisation was correlated to lower abundances of spiders and springtails, but higher abundances of aphids, barklice and flies. Arthropod community composition was better explained by a set of urbanisation proxies, especially impervious surface cover measured in a 100 m, 500 m and 1000 m radius. Arthropods are key elements of food webs and their availability in urban environments is expected to have bottom-up effects, thus shaping foraging behaviour, distribution, and/or success of species at higher trophic levels. Studying ecological networks in urban ecosystems is the next step that will allow to understand how urbanisation alters biodiversity.